E-government and e-democracy - Netchaeva, Irina (2002)
Analyses the possibilities and obstacles to using the Internet to promote democracy in different regions. Compares the situation of e-government and democracy in the North and South. Focuses in particular on South Africa's experience, as a country which lives in both the developed and developing world at the same time.